2023
DOI: 10.1186/s40580-022-00350-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gut microbiome-derived metabolites and extracellular vesicles on hepatocyte functions in a gut-liver axis chip

Abstract: Metabolism, is a complex process involving the gut and the liver tissue, is difficult to be reproduced in vitro with conventional single cell culture systems. To tackle this challenge, we developed a gut-liver-axis chip consisting of the gut epithelial cell chamber and three-dimensional (3D) uniform-sized liver spheroid chamber. Two cell culture chamber compartments were separated with a porous membrane to prevent microorganisms from passing through the chamber. When the hepG2 spheroids cultured with microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Via microbial EVs, the biomolecules within the microbiota are transferred to other tissues, organs, or cells of the host to modulate the synthesis and secretion of proteins, nucleic acids, lipids, or other metabolites in the recipient cells. However, the impacts of different strains of microbiota on the host exhibit some degrees of uncertainty and diversity [ 105 ]. Some bacteria-derived EVs contain proteins capable of modulating the host immune system, but the content of these substances is contingent upon the classification and specific characteristics of the parent species [ 74 ].…”
Section: Microbiome–gut–brain Axismentioning
confidence: 99%
“…Via microbial EVs, the biomolecules within the microbiota are transferred to other tissues, organs, or cells of the host to modulate the synthesis and secretion of proteins, nucleic acids, lipids, or other metabolites in the recipient cells. However, the impacts of different strains of microbiota on the host exhibit some degrees of uncertainty and diversity [ 105 ]. Some bacteria-derived EVs contain proteins capable of modulating the host immune system, but the content of these substances is contingent upon the classification and specific characteristics of the parent species [ 74 ].…”
Section: Microbiome–gut–brain Axismentioning
confidence: 99%
“…Its two chambers are separated by a porous membrane to let the hepatocytes in but inhibit microorganisms entering the chamber. 373 Nano-poly-boronic acid regulates sugar intake and liver lipogenesis, and finally prevents fructose and glucose absorption in the gut. 374 In addition, certain microorganisms' components are prepared into nanotechnology like light-sensitive Lactococcus lactis which is an oral live biotherapeutic agent that makes communication from the gut to the host more manageable.…”
Section: Mechanisms Linking the Liver-brain Axismentioning
confidence: 99%
“…Moreover, seminal studies have demonstrated the crucial role of gut microbiome in influencing several disease conditions (Bull & Plummer, 2014; Clemente et al., 2012; de Vos et al., 2022; Hou et al., 2022; Li et al., 2008; Vijay & Valdes, 2022). The imbalance of the gut microbiota, referred to as gut dysbiosis, has been associated with biological effects in distant organs, leading to the identification of microbiota‐gut‐brain, microbiota‐gut‐lung, microbiota‐gut‐liver and microbiota‐gut‐skin axes (Giridharan et al., 2022; Kang et al., 2023; Varela‐Trinidad et al., 2022). These gut‐organ axes are bi‐ or multi‐directional, or multi‐channel communications that allow the gut and extra‐intestinal organs to communicate with one another and dictate the effect of the gut microbiome on human health.…”
Section: Introductionmentioning
confidence: 99%